Design of pulsatile flow bioreactor system for tissue engineering application using LabVIEW - Zaw Zaw Htun (2009)
Pulsatile flow bioreactor system is important for maintaining cardiovascular cells under dynamic physical forces for vasculogenesis, homogeneous tissue formation and improved mechanical properties of tissue constructs. However, a simple, versatile and easy to manage bioreactor system is currently not available. This project aimed to design and develop a pulsatile flow bioreactor system suitable for application in the engineering cardiocascular system. A system incorporating LabVIEW programs and peristaltic pump(s) for reproducing physiological flow waveforms has been developed. The system was tested by reproducing the human right coronary artery, the left anterior descending coronary artery and the aortic flow waveforms. Two types of LabVIEW programs were developed. One can duplicate the waveforms by using their general equations. The other can reproduce the waveforms by using data points extracted from the available physiological flow waveforms. The performance of the bioreactor system, in term of producing duplicated waveforms was limited by the low response frequency of the pump. It performed best with 41 data points in the input waveform. On the whole, the bioreactor system performed satisfactorily, based on a simple evaluation experiment, generating an average output flow rate to be within 94% of the flow rate requested or input into the programs. The developed pulsatile bioreactor system is versatile and expected to be useful in producing physiological flows for cell and tissue stimulation. It is suggested, however, that a suitable flow probe, LabVIEW program, and a pump system with higher response frequency should be incorporated to further improve the performance of the system.